Satuan Lingual dalam Aktivitas Perkebunan Kopi pada Tahap Prapanen di Kebun Kopi Banaran: Kajian Semantik - Suryana Rochman; Nur Fateah; Eka Yuli Astuti (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2026)
Communication is a common practice among humans as social beings. Naturally, communication requires language as a means to convey information. This is particularly true for communication within a professional group, which relies on language as a primary component for information delivery. This study focuses on a cultural semantic analysis, with the workers at the Banaran Coffee Plantation serving as the language speakers. The purpose of this research is to identify, classify, and describe the lingual units used by the workers during the pre-harvest stage, according to their respective forms and meanings. A qualitative descriptive approach was selected to systematically and factually describe the linguistic phenomena based on field data. The results of this study indicate that there are 29 lingual units used by the workers at the Banaran Coffee Plantation. The forms of these lingual units consist of 21 words, 6 phrases, and 3 abbreviations. The lexical meaning of the lingual units used by the workers at the Banaran Coffee Plantation is exemplified by the word nglobang, which corresponds to the ongoing activity of the farmers. Meanwhile, the cultural meaning is found in the term teras iring, which holds a specific connotation for the workers at the Banaran Coffee Plantation.